﻿ Find the natural number a for which  where the function f satisfies the relation f (x + y) = f (x) f (y) for all natural number x, y and further f (1) = 2.   : Kaysons Education

# Find The Natural Number a for Which  where The Function f satisfies The Relation f (x + y) = f (x) f (y) For All Natural Number x, y and Further f (1) = 2.

#### Video lectures

Access over 500+ hours of video lectures 24*7, covering complete syllabus for JEE preparation.

#### Online Support

Practice over 30000+ questions starting from basic level to JEE advance level.

#### National Mock Tests

Give tests to analyze your progress and evaluate where you stand in terms of your JEE preparation.

#### Organized Learning

Proper planning to complete syllabus is the key to get a decent rank in JEE.

#### Test Series/Daily assignments

Give tests to analyze your progress and evaluate where you stand in terms of your JEE preparation.

## Question

### Solution

Correct option is

a = 3

Since the function satisfies the relation

f (y) = f (xf (y)

It must be an exponential function.

Let the base of this exponential function be a.

Thus f (x) = ax

It is given that f (1) = 2. So we can make

f (1) = a1 = 2 ⇒     a = 2

Hence, the function is f (x) =2x                    … (i)

[Alternatively, we have]

f (x) = f (x – 1 + 1) = f (x – 1) f (1)

= f (x – 2 + 1) f (1)

= f (x – 2) [f (1)]2 = … = [f (1)]x = 2x]

Using equation (i), the given expression reduces to:

#### SIMILAR QUESTIONS

Q1

Discuss the continuity of the function .

Q2

Let f : → R, such that f’ (0) = 1 and f (x +2y) = f (x) + f (2y) + ex+2y (x + 2y) – x. ex – 2y. e2y + 4xy∀ xy Ïµ R. Find f (x).

Q3

If g(x) is continuous function in [0, ∞) satisfying g(1) = 1. If

.

Q4

Let f is a differentiable function such that

.

Q5

Let f : R+ → R satisfies the functional equation

.

If f’(1) = e, determine f (x).

Q6

Let f is a differentiable function such that

.

Q7

Let f be a function such that  .

.

Q8

Find and b so that the function:

Q9

is continuous at x = 0, find the values of Aand B. Also find f (0).

Q10

Find the derivative of y = log x wrt x from first principles.